Wasiyyah Wajibah in Islamic estate planning: an analysis - Habibur Rahman, Muhammad; Monawer, Abu Talib Muhammad; Osmani, Noor Mohammad (UNISZA, 2020)
Wasiyyah wajibah (binding will) is legislated by the law for unprivileged grandchildren due to death of their father during the lifetime of grandfather whereas other grandchildren, i.e. cousins, stay solvent. Contemporary Muslim scholars disagree on the obligatory status and category of inheritors of wasiyyah wajibah as well as confusion appears over its consumption among Muslim society. Hence, this study using an analytical method, aims to examine the legitimacy of wasiyyah wajibah and its parameters. The most important finding of this study is that wasiyyah wajibah is legitimate due to grandchildren’s sustenance and it is binding (wajibah) due to the authority of law as the judgment of ruler settles the dispute. Thus its legitimacy abides by the general principles of Islamic law. The study also concludes that the obligation of wasiyyah has been abrogated by the verse of inheritance only for the parents and relatives who inherit from the deceased’s legacy, not for the parents and relatives who are deprived from the deceased. Wasiyyah wajibah shall abide by the fundamentals of wasiyyah in Islamic law and the deceased’s volume of legacy will be the benchmark of the portion of grandchildren. Finally, wasiyyah wajibah signify the social justice and social solidarity of Islamic inheritance law (fara’id).